Letter (copy) : Goods for Spain - Tewson, Vincent
030-0136-001 Secretary's HVT/FC/EK/1391. EXPORT ST/HP. 1179. 28th June, 1938. Mr. E. Winstanley, Export Department, Co-operative Wholesale Society Limited, 1, Balloon Street, MANCHESTER, 4. Dear Mr. Winstanley, GOODS FOR SPAIN. I have your letter of the 27th instant enclosing invoice amounting to £787.10.0. in respect of dried cod shipped per s.s. "C.W.S. PROGRESS". This is receiving our attention. Yours sincerely, Assistant Secretary. 292/946/30/136